Evaluating Nutritional Standards and Fiscal Sustainability in Free School Meal Programs - Ryanta, Naufal Faryreza; Asri, Salsabila Najwa; Gabela, Jita; Ramadhani , Salsabila; Yanti, Putri (Inspirasi Foundation, 2026)
Introduction: Childhood obesity is a global health emergency that threatens the quality of Indonesia's human resources. Indonesian Health Survey (IHS) recorded an increase in adult obesity prevalence from 23.4% to 21.8% in 2018. National indicators estimate that approximately 18.8% of children aged 5-12 years are overweight and 10.8% are obese. Objective: This study aims to evaluate the impact of Ultra-Processed Foods (UPF) on the Makan Bergizi Gratis (MBG) program through an integration of public health, nursing, Islamic psychology, and accounting perspectives. Method: The method used was a narrative literature review with an electronic literature search in Google Scholar, PubMed, SINTA, and ScienceDirect databases for the 2019–2026 period. Result: The results show that UPF triggers biological sabotage through insulin resistance and disruption of the leptin-ghrelin hormone. Psychoneurobiologically, the hyperpalatable nature of UPF hijacks the brain's reward system, triggering food addiction. Implementation analysis revealed a fatal food safety gap that resulted in 5,620 student food poisoning and a crisis of public trust due to low dietetic standards in the field. From an accounting perspective, the use of UPF constitutes a